Soil-applied Zn effect on soil fractions - Leite, Camila Marcon de Carvalho (2020)
The interaction of Zn with soil compartments influences its bioavailability and uptake by plants. In this study, rice and soybean were cultivated under greenhouse conditions with the aim of evaluating Zn bioavailability and fractionation in a clayey-textured Typic Hapludox as a function of Zn rates (4 or 8 mg kg–1 Zn). The experiment was conducted until grain filling. Two soil subsamples (t1 and t2) that referred to the seeding and flowering stages, were collected and compared with two single extraction schemes, DTPA (ZnDTPAt1 and ZnDTPAt2) and Mehlich-1 (ZnMt1 and ZnMt2) for Zn available contents. Zn fractionation was carried out with t2 soil subsamples for the testing of the following fractions: exchangeable Zn (ZnExc), Zn bound to carbonates (ZnCarb), Zn bound to organic matter (ZnOM), Zn bound to oxides (ZnOxi) and residual Zn (Znres). Zn applied to soil increased the Zn concentration in labile fractions in decreasing order as follows: ZnExc > ZnOM > ZnCarb. There was no difference between the lesser or unavailable fractions, ZnOxi and Znres, when there was no correlation between the rates either with total accumulated Zn in plants (Znatotal), or the contents extracted by DTPA or Mehlich-1. Total cumulative Zn content in rice and soybean affected by the ZnCl2 rates applied were positively correlated with Zn content extracted by both solutions. Both extractant solutions presented positive correlation between available contents of Zn with Zn bound to labile fractions.